2018
DOI: 10.1002/sia.6448
|View full text |Cite
|
Sign up to set email alerts
|

Improved interfacial properties of PI composites through graphene oxide and carbon nanotubes on carbon fiber surface

Abstract: Carbon nanotubes (CNTs) have been identified as excellent nanoreinforcements for carbon fiber (CF)-reinforced polymers regarding a wide range of engineering applications. The outstanding properties of CNTs, such as their large surface area, high mechanical strength, and low manufacturing cost bring them to be distinguished nanoreinforcements for carbon fiber-reinforced polymers to form multifunctional and multiscale composites. Electrophoretic deposition of graphene oxide for CNTs onto the CF surface was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
1
5
0
Order By: Relevance
“…are even much better . Peng et al reported the poor interfacial adhesion between CFs and PI, in agreement with the investigation of lv et al In spite of these findings, the mechanism for the influence of the PI sizing agent on interfacial properties of CF/PEEK composites is still not fully understood. Furthermore, as a typical semi‐crystalline polymer, the interfacial crystalline behavior of PEEK is a critical parameter governing the overall performance of CF/PEEK composites.…”
Section: Introductionsupporting
confidence: 73%
See 1 more Smart Citation
“…are even much better . Peng et al reported the poor interfacial adhesion between CFs and PI, in agreement with the investigation of lv et al In spite of these findings, the mechanism for the influence of the PI sizing agent on interfacial properties of CF/PEEK composites is still not fully understood. Furthermore, as a typical semi‐crystalline polymer, the interfacial crystalline behavior of PEEK is a critical parameter governing the overall performance of CF/PEEK composites.…”
Section: Introductionsupporting
confidence: 73%
“…are degraded during processing at such high temperature, new sizing agents with high thermal stability have drawn great attention, in particular polyimide (PI) . PI sizing agents have many advantages including partial compatibility with PEEK, excellent mechanical properties, and endurance of high temperature . Thus, many researchers have tried to introduce PI sizing agents into CF surfaces; however, the results are not desirable yet.…”
Section: Introductionmentioning
confidence: 99%
“…These improvements were attributed to the excellent progress in the chemical and mechanical interaction (interlocking) between GO on the surface of CF and the PP matrix as superior interfacial bonding. Yongqiang et al [76] deposited CNTs and GO on CF. They reported an enhancement in the interfacial adhesion, roughness, and wettability of the CF surface to increase adhesion between the PI matrix and the CF due to hydrogen bonding and mechanical interlocking.…”
Section: Physical Treatmentsmentioning
confidence: 99%
“…26 Better interfacial performance of composites can be achieved through uniform distribution of CNTs on CF. 27 However, the strong Van der Waals' attracted force among functionalized CNTs will lead to significant self-aggregation, making good dispersion difficult. 28 Some researchers focused on combining dendritic polymers and functionalized CNTs to achieve the desired treated effect for CF.…”
Section: Introductionmentioning
confidence: 99%